Who Is a Jew and Who Is a Gentile in the Book of Acts? - Sanders, Jack T. (New Testament studies, 1991)
It has been now nearly a quarter century since W. C. van Unnik labelled the two-volume work to which we refer in abbreviated form as Luke–Acts as ‘a storm center in contemporary scholarship’. He referred in particular to the issues of redaction criticism, of the purpose of Acts, of the theological approach in Luke–Acts to the problem of the delay of the parousia, of the author's treatment of Paul, of the character and function of the speeches in Acts, and of whether it was proper to refer to the theological position of Luke–Acts as ‘early Catholic’ and therefore, in the minds of the German Lutheran theologians who were raising that question, as degraded, fallen from the early purity of Paul's Christianity, and unworthy of theological consideration today.